Hukum Penggunaan Filter Wajah Dan Identitas Virtual Dalam Fikih Kontemporer - Robi'ah, Robi'ah (Universitas Pakuan, 2026)
THE LEGAL STATUS OF USING FACE FILTERS AND VIRTUAL IDENTITIES IN CONTEMPORARY FIQHDigital technology has introduced new forms of social interaction, including the use of face filters and virtual identity representation. Previous studies have mainly focused on the general impact of social media, but have not comprehensively examined the legal and ethical aspects of face filter usage and virtual identities within contemporary Islamic jurisprudence. This study aims to explore the phenomenon of virtual identity, review fiqh perspectives on digitally modified appearances, and analyze ethical concerns related to honesty and identity deception. The research applied a qualitative literature-based method with descriptive analysis. The findings show that the use of face filters is conditionally permissible: it is acceptable as long as it does not lead to deception, moral degradation, or harm; and prohibited when it alters identity to the point of deception, causing social harm or violating Islamic principles of honesty. This study highlights the importance of digital ethics and moral awareness in responsibly utilizing modern technological tools.